A escrita e a escritura em S. Bernardo, de Graciliano Ramos: a confluência das memórias e dos olhares - Flauzino, Valter Donizete (2012)
The main objective of this research is to study the significative implications between memory and writing, on novel S. Bernardo (1934), by Graciliano Ramos, emphasizes the process of the act of writing and, in it, the relations between memory and lookings. To guide this subject, we propose some critical hypotheses over essays written by Antonio Candido, João Luiz Lafetá, Wander Melo Miranda and Luís Bueno, in which these writers exceed the importance of writing to understand the novel. When the chief character narrator, Paulo Honório, gets in the representation of last lifetime, by the act of writing, he reaches the actual moment to review his actions, and facts of the past and, therefore, to correct his perspectives, ideas and values. To the conduct the reading again his past experiences, and to get in the understanding of his reality, the narrator obtains the possibility to know himself, to aware himself of the effects of his past actions, to know about the fusion of his memories to Madalena ones, and other characters, and, mainly, to embody the essence, and the metamorphosis of the impulsive man in dreamer one. We also guide to the studies about memory, according to Henry Bergson, Paul Ricoeur and Maurice Halbwachs, besides the theories about writings of Maurice-Jean Lefebve, Maurice Blanchot, and other ones. The research results have shown us the passage of writing to the act, and of how the writing of S. Bernardo established the process of metamorphosis of the character Paulo Honório. So, Paulo Honório moves from of condition of impulsive man to the dreamer one, and, by the act of writing, he becomes an evocative man. He gets in, under the poetic essence, in the universe of writing, built by possibilities, and by the no paths of the composition of his memorial book